EFFECT OF APPLICATION OF STATIC MAGNETIC FIELDS USING THE DOUBLE MAGNET OF MEDICINAL BIOMAGNETISM IN DYSMENORRHEA: CASE REPORTS - Aparecida Cintra, Ana; Januaria Silva, Delma; Maria Oliveira Lima, Marcia; Viapiana Bossa, Adriane; Mara Rambo Martini, Angela (Health and Society, 2023)
Introduction: Menstrual colic, or dysmenorrhea, is a common gynecological complaint characterized by pelvic cramp-like pain before or during menstruation. Medicinal Biomagnetism (BM) is a complementary and integrative method that may help in the treatment and prevention of dysmenorrhea symptoms. It aims to restore the energetic balance and ideal pH of the area impacted by medium-intensity therapeutic magnets. Objective: To investigate the effect of the Double BM Magnet on acute menstrual colic pain. Methodology: A case study involving two participants where the Double BM Magnet protocol was applied to address dysmenorrhea, assessed using the Visual Analog Scale. Results: It was observed that the Double BM Magnet tool generated an analgesic effect on menstrual colic pain, providing a significant result within 60 minutes of its application. Conclusion: This study suggests that the application of the Double BM Magnet in the pelvic region for the relief of menstrual pain can have a significant analgesic effect. It proves to be relevant due to its ease of application, non- invasiveness, low cost, and the possibility of self-application. Furthermore, it has minimal contraindications and rare side effects.